Foamable methyl methacrylate resin particles, methyl methacrylate foamed particles, methyl methacrylate foamed molded body, and lost foam

By adjusting the particle size and composition of foamable methyl methacrylate resin particles, the problems of surface quality and combustion residue in the prior art are solved, and excellent foaming, filling and shrinking are achieved, and suitable for high quality metal casting disappears mold.

CN115380064BActive Publication Date: 2024-12-13KANEKA CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180025426.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-03-04
Publication Date
2024-12-13
Estimated Expiration
2041-03-04

AI Technical Summary

Technical Problem

The foamable methyl methacrylate resin particles have room for improvement in surface quality and residue during combustion, especially the problems of poor filling and large shrinkage.

Method used

Foaming methyl methacrylate-based resin particles with an average volume particle diameter of 0.30mm to 0.50mm are used. The base resin contains methyl methacrylate, acrylate and crosslinker structural units, and the content ratio is 90.0 to 99.0 %, 1.0 to 10.0% and 0.05 to 0.20%, and an aromatic vinyl compound is added to prepare particles with excellent foaming, fillability and shrinkability.

Benefits of technology

A foamed molded body with excellent surface quality and few residues during combustion is achieved, and is suitable for vanishing molds in the whole mold casting method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005038375640000251
    Figure GDA0005038375640000251
  • Figure GDA0005038375640000261
    Figure GDA0005038375640000261
Patent Text Reader

Abstract

The object is to provide a foamable methyl methacrylate resin particle which can provide a foamed molded article with excellent surface quality and little residue when burned. Provided is a foamable methyl methacrylate resin particle comprising a base resin and a foaming agent, and having a volume average particle size of 0.30 mm to 0.50 mm, wherein the base resin comprises, as a structural unit, specific amounts of methyl methacrylate units, acrylate units, and structural units derived from a crosslinking agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to expandable methyl methacrylate resin particles, methyl methacrylate expandable particles, methyl methacrylate expandable molded bodies and lost foams. Background Art

[0002] When metal casting is performed, the following lost foam casting method (full mold casting method) is known: a mold made of a foamed molded body is buried in casting sand, molten metal is flowed into the foamed molded body to replace the foamed molded body with the metal, thereby casting a casting. In the full mold casting method, from the viewpoint of reducing the residue during casting, a foamed molded body of a methyl methacrylate polymer is used.

[0003] As the prior art of expandable methyl methacrylate resin particles for producing a foamed molded article of methyl methacrylate polymer, there are the technologies shown in the following Patent Documents 1 and 2. Patent Document 1 discloses expandable methyl methacrylate resin particles having a particle size of 0.5 to 1.4 mm, which are obtained by polymerizing methyl methacrylate, acrylic acid ester and a multifunctional monomer.

[0004] Patent Document 2 discloses expandable methyl methacrylate resin particles having an average particle size of 0.3 to 0.5 mm, which are obtained by suspension polymerization of a mixture of a methacrylate monomer and a styrene compound.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. WO2016 / 047490

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 2003-261603 Summary of the invention

[0009] Problem that the invention aims to solve

[0010] However, the above-mentioned conventional techniques still have room for improvement from the viewpoints of the surface quality of the foamed molded article provided by the foamable methyl methacrylate resin particles and the reduction of the residues when the foamed molded article is burned.

[0011] In view of the above circumstances, an object of one embodiment of the present invention is to provide a novel expandable methyl methacrylate resin particle capable of providing an expanded molded article having excellent surface quality and less residue during combustion.

[0012] Solutions for solving problems

[0013] The inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention.

[0014] The expandable methyl methacrylate resin particles according to one embodiment of the present invention include a base resin and a foaming agent, and have a volume average particle size of 0.30 mm to 0.50 mm. The base resin includes a methyl methacrylate unit, an acrylate unit, and a structural unit derived from a crosslinking agent as structural units. In the base resin, (a) the content of the methyl methacrylate unit is 90.0 to 99.0 parts by weight, and the content of the acrylate unit is 1.0 to 10.0 parts by weight, relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, (b) the content of the structural unit derived from the crosslinking agent is 0.05 parts by weight or more and less than 0.20 parts by weight, relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, and (c) the content of the structural unit derived from an aromatic vinyl compound is 2.5 parts by weight or less, relative to 100 parts by weight of the base resin.

[0015] Effects of the Invention

[0016] According to one embodiment of the present invention, there is provided an effect of being able to provide expandable methyl methacrylate resin particles capable of providing an expanded molded article having excellent surface quality and less residue during combustion. DETAILED DESCRIPTION

[0017] An embodiment of the present invention is described below, but the present invention is not limited thereto. The present invention is not limited to the various configurations described below, and various changes can be made within the scope indicated by the claims. In addition, embodiments or embodiments obtained by combining the technical means disclosed in different embodiments or embodiments are also included in the technical scope of the present invention. Furthermore, by combining the technical means disclosed in each embodiment, new technical features can be formed. It should be noted that all the academic literature and patent documents recorded in this specification are cited in this specification as references. In addition, unless otherwise specified in this specification, the meaning of "A to B" indicating a numerical range is "above A (including A and greater than A) and below B (including B and less than B)".

[0018] In this specification, “expandable methyl methacrylate resin particles” may be referred to as “expandable resin particles”, “methyl methacrylate foamed particles” may be referred to as “foamed particles”, and “methyl methacrylate foamed molded article” may be referred to as “foamed molded article”.

[0019] [1. Technical concept of one embodiment of the present invention]

[0020] As a result of studies, the present inventors have found that there is still room for improvement in the expanded molded article obtained using the expandable resin particles disclosed in Patent Documents 1 and 2 from the viewpoints of surface quality and reduction of residues during combustion.

[0021] For example, the expandable methyl methacrylate resin particles described in Patent Document 1 have a large particle size. Therefore, when a molded body is produced using the expandable methyl methacrylate resin particles, the expandable particles have poor filling properties in thin-walled locations (narrow locations in the mold). As a result, a molded body having poor surface aesthetics is obtained using the technology described in Patent Document 1.

[0022] In order to improve the surface smoothness, the foamed molded article of methyl methacrylate polymer described in Patent Document 2 contains a styrene component. The present inventors independently found that the foamed molded article containing a styrene component generates residues during combustion, which adversely affects the quality of the casting.

[0023] In view of the above circumstances, one embodiment of the present invention is to provide expandable methyl methacrylate resin particles, methyl methacrylate expanded particles, and methyl methacrylate expanded molded articles having excellent expandability, filling property, and shrinkage property.

[0024] The inventors independently discovered the following problems: (1) the methyl methacrylate foamed particles obtained by foaming foamable methyl methacrylate resin particles having a large volume average particle size have poor filling properties in a mold; (2) the foamable methyl methacrylate resin particles having a small volume average particle size have poor foaming properties; (3) the methyl methacrylate foamed particles obtained by foaming foamable methyl methacrylate resin particles having a small volume average particle size have large shrinkage during molding; and (4) as a result of the above (2) and (3), the surface quality of the foamed molded article obtained by in-mold molding of the methyl methacrylate foamed particles is poor. The inventors conducted intensive studies focusing on the problems independently discovered and completed the present invention.

[0025] [2. Foamable methyl methacrylate resin particles]

[0026] The expandable methyl methacrylate resin particles according to one embodiment of the present invention include a base resin and a foaming agent, and the volume average particle size thereof is 0.30 mm to 0.50 mm. The base resin includes a methyl methacrylate unit, an acrylate unit, and a structural unit derived from a crosslinking agent as structural units. In the base resin, (a) the content of the methyl methacrylate unit is 90.0 to 99.0 parts by weight, and the content of the acrylate unit is 1.0 to 10.0 parts by weight, relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, (b) the content of the structural unit derived from the crosslinking agent is 0.05 parts by weight or more and less than 0.20 parts by weight, relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, and (c) the content of the structural unit derived from an aromatic vinyl compound is 2.5 parts by weight or less, relative to 100 parts by weight of the base resin.

[0027] Hereinafter, “expandable methyl methacrylate resin particles according to one embodiment of the present invention” may be referred to as “present expandable resin particles”.

[0028] By expanding the present expandable resin particles by a known method, expandable particles can be provided. By in-mold molding the expandable particles obtained by expanding the present expandable resin particles by a known method, an expandable molded article can be provided.

[0029] The present foamable resin particles have the aforementioned structure, and therefore have the advantage of being able to provide a foaming molded body with excellent surface quality and little residue during combustion. In this specification, the surface quality of the foaming molded body is described in the following embodiments and evaluated by the surface aesthetics of the foaming molded body. The surface quality of the foaming molded body will be affected by the foamability of the foamable resin particles as the raw material of the foaming molded body, and the filling property and shrinkage of the foaming particles. The more excellent the foamability of the foamable resin particles, and the filling property and shrinkage of the foaming particles, the more excellent the surface quality of the foaming molded body. Therefore, the present foamable resin particles have the aforementioned structure, and therefore have the advantages of (a) excellent foamability and (b) being able to provide foaming particles with excellent filling property and shrinkage.

[0030] (Base resin)

[0031] The base resin contained in the present foamable resin particles contains methyl methacrylate units, acrylate units and structural units derived from a crosslinking agent as structural units. In this specification, "methyl methacrylate unit" refers to a structural unit derived from a methyl methacrylate monomer, and "acrylate unit" refers to a structural unit derived from an acrylate monomer. In this specification, the expression "monomer" is sometimes omitted. Therefore, in this specification, for example, when only "methyl methacrylate" and "acrylate" are expressed, they represent "methyl methacrylate monomer" and "acrylate monomer", respectively.

[0032] In the base resin contained in the present expandable resin particles, relative to 100 parts by weight of the total amount of methyl methacrylate units and acrylate units, (a) the content of methyl methacrylate units is 90.0 parts by weight to 99.0 parts by weight, and the content of acrylate units is 1.0 parts by weight to 10.0 parts by weight; preferably (b) the content of methyl methacrylate units is 91.0 parts by weight to 99.0 parts by weight, and the content of acrylate units is 1.0 parts by weight to 9.0 parts by weight, and more preferably (c) the content of methyl methacrylate units is 92.0 parts by weight to 97.0 parts by weight. , and the content of acrylate units is 3.0 to 8.0 parts by weight; more preferably (d) methyl methacrylate is 93.0 to 96.0 parts by weight, and acrylate is 4.0 to 7.0 parts by weight, further preferably (e) the content of methyl methacrylate units is 94.0 to 96.0 parts by weight, and the content of acrylate units is 4.0 to 6.0 parts by weight, and particularly preferably (f) the content of methyl methacrylate units is 94.5 to 95.0 parts by weight, and the content of acrylate units is 5.0 to 5.5 parts by weight. In the base resin, when the content of methyl methacrylate units is greater than 99.0 parts by weight relative to the total amount of methyl methacrylate units and acrylate units of 100 parts by weight, the foamable resin particles tend to have poor foamability and formability. As a result, it is difficult for the foamable resin particles to provide a foamed molded body with excellent surface quality. When the content of the acrylic acid ester unit in the base resin exceeds 10 parts by weight relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylic acid ester unit, the foamed beads tend to shrink easily.

[0033] As an acrylate of one embodiment of the present invention, methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, etc. can be cited. As the acrylate, butyl acrylate is particularly preferred. In other words, the acrylate unit is particularly preferably a butyl acrylate unit derived from a butyl acrylate monomer. Butyl acrylate has a strong effect of lowering the glass transition temperature of the base resin. Therefore, by this configuration, foamable resin particles with excellent foamability can be provided.

[0034] The base resin of the present expandable resin particles contains a structural unit derived from a crosslinking agent. The base resin of the present expandable resin particles contains a structural unit derived from a crosslinking agent, and the expandable resin particles can provide expandable particles having excellent shrinkage properties.

[0035] As a crosslinking agent, for example, a compound having two or more functional groups showing free radical reactivity can be cited. Among the compounds having two or more functional groups showing free radical reactivity, as a crosslinking agent, a difunctional monomer having two functional groups is preferably used. In other words, the base resin of the present foamable resin particles preferably contains a structural unit derived from a difunctional monomer, i.e., a difunctional monomer unit as a structural unit derived from a crosslinking agent. Through this structure, there are the advantages of (a) excellent foamability of the foamable resin particles, (b) excellent shrinkage of the foamed particles formed by foaming the foamable resin particles, and (c) excellent surface quality of the foamed molded body formed by in-mold molding of the foamed particles.

[0036] As the difunctional monomer, for example, there can be mentioned (a) compounds in which the two terminal hydroxyl groups of ethylene glycol or the oligomer of ethylene glycol are esterified with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, etc.; (b) compounds in which the hydroxyl groups of dihydric alcohols are esterified with acrylic acid or methacrylic acid, such as neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate, butanediol di(meth)acrylate, etc.; and (c) aromatic compounds having two alkenyl groups, such as divinylbenzene, etc. Since hexanediol di(meth)acrylate is easy to adjust the molecular weight of the base resin, hexanediol di(meth)acrylates such as 1,6-hexanediol diacrylate are preferred as difunctional monomers. In this specification, "(meth)acrylate" means methacrylate and / or acrylate.

[0037] In the base resin, relative to the total amount of methyl methacrylate units and acrylate units of 100 parts by weight, the content of the structural unit derived from the crosslinking agent is 0.05 parts by weight or more and less than 0.20 parts by weight, preferably 0.05 parts by weight to 0.19 parts by weight, more preferably 0.05 parts by weight to 0.17 parts by weight or less, more preferably 0.08 parts by weight to 0.15 parts by weight or less, and further preferably 0.08 parts by weight to 0.13 parts by weight. Through the above-mentioned structure, there are the advantages of (a) excellent foaming property of the foamable resin particles, (b) excellent shrinkage of the foamed particles formed by foaming the foamable resin particles, and (c) excellent surface quality of the foamed molded body formed by in-mold molding of the foamed particles. Through the above-mentioned structure, the foamed molded body has the advantages of excellent strength and less residue during combustion.

[0038] The base resin of the present foamable resin particles may also contain a structural unit derived from an aromatic vinyl compound as a structural unit. As the aromatic vinyl compound, styrene, α-methylstyrene, p-methylstyrene, tert-butylstyrene and chlorostyrene can be mentioned. When the base resin of the present foamable resin particles contains a structural unit derived from an aromatic vinyl compound, a foaming molding with excellent strength can be obtained.

[0039] From the viewpoint of the foaming molding that the residue when obtaining combustion is few, the amount of the structural unit derived from the aromatic vinyl compound in the substrate resin is preferably as little as possible. In the substrate resin, relative to 100 weight parts of substrate resin, the content of the structural unit derived from the aromatic vinyl compound is below 2.5 weight parts, preferably less than 2.5 weight parts, more preferably below 2.0 weight parts, more preferably below 1.5 weight parts, further preferably below 1.0 weight parts, particularly preferably 0 weight part. That is, the substrate resin of this foamable resin particle is particularly preferably not containing the structural unit derived from the aromatic vinyl compound.

[0040] (foaming agent)

[0041] The foaming agent contained in the foamable resin particles is not particularly limited. Examples of the foaming agent include (a) aliphatic hydrocarbons such as propane, isobutane, n-butane, isopentane, n-pentane, and neopentane, which are hydrocarbons having a carbon number of 3 or more and 5 or less, and (b) volatile foaming agents such as difluoroethane and tetrafluoroethane, which have an ozone depletion coefficient of 0, such as hydrofluorocarbons. These foaming agents may be used alone or in combination of two or more.

[0042] In the present expandable resin particles, the content of the foaming agent is preferably 5 to 12 parts by weight, more preferably 7 to 10 parts by weight, relative to 100 parts by weight of the expandable methyl methacrylate resin particles. This configuration has the advantage of providing expandable resin particles having sufficient expandability without requiring heavy polymerization equipment.

[0043] (Other additives)

[0044] The expandable resin particles may optionally contain other additives in addition to the base resin and the foaming agent. Examples of the other additives include solvents, plasticizers, bubble regulators, flame retardants, flame retardant aids, thermal radiation inhibitors, pigments, dyes, and antistatic agents.

[0045] The solvent is not particularly limited, but a solvent having a boiling point of 50°C or above is preferred. Examples of solvents having a boiling point of 50°C or above include (a) aliphatic hydrocarbons having a carbon number of 6 or more (C6 or more), such as toluene, hexane, and heptane, and (b) alicyclic hydrocarbons having C6 or more, such as cyclohexane and cyclooctane. From the perspective of obtaining foamable resin particles having excellent foamability, toluene and / or cyclohexane are preferred as solvents having a boiling point of 50°C or above. In the present foamable resin particles, the content of the solvent is preferably 1.5 to 3.0 parts by weight relative to 100 parts by weight of the substrate resin. When the content (a) of the solvent is 1.5 parts by weight or more relative to 100 parts by weight of the substrate resin, foamable resin particles having sufficient foaming power can be obtained, and when (b) is 3.0 parts by weight or less, a foamed molded body having suppressed surface expansion, i.e., excellent dimensional stability, can be obtained.

[0046] The plasticizer is not particularly limited, but a high boiling point plasticizer having a boiling point of 200° C. or higher is preferred. Examples of the high boiling point plasticizer include (a) fatty acid glycerides such as stearic acid triglyceride, palmitic acid triglyceride, lauric acid triglyceride, stearic acid diglyceride, and stearic acid monoglyceride; (b) vegetable oils such as coconut oil, palm oil, and palm kernel oil; (c) aliphatic esters such as dioctyl adipate and dibutyl sebacate; and (d) organic hydrocarbons such as liquid paraffin and cyclohexane.

[0047] In the present foamable resin particles, the content of the plasticizer is preferably 0.40 to 4.00 parts by weight, preferably 0.50 to 3.50 parts by weight, more preferably 0.60 to 3.00 parts by weight, more preferably 0.70 to 2.70 parts by weight, more preferably 0.80 to 2.40 parts by weight, more preferably 0.90 to 2.10 parts by weight, further preferably 1.00 to 1.80 parts by weight, and particularly preferably 1.20 to 1.50 parts by weight, relative to 100 parts by weight of the base resin. This configuration has the advantages that the foamable resin particles are excellent in foamability and the foamable resin particles can provide foamable particles with excellent shrinkage.

[0048] Examples of the cell control agent include (a) aliphatic bisamides such as methylene bisstearic acid amide and ethylene bisstearic acid amide, and (b) polyethylene wax.

[0049] (Weight average molecular weight)

[0050] The weight average molecular weight of the expandable resin particles measured by gel permeation chromatography (GPC) and calculated as polystyrene is preferably 100,000 to 400,000. With this configuration, an expanded molded article having excellent surface quality and little residue during combustion can be obtained.

[0051] (Volume average particle size)

[0052] The volume average particle size of the foamable resin particles is 0.30 mm to 0.50 mm, preferably 0.35 to 0.45 mm, and more preferably 0.40 mm to 0.45 mm. When the volume average particle size of the foamable resin particles is less than 0.30 mm, the foamable resin particles will lead to a decrease in foamability during foaming and / or an increase in the amount of adhesion during foaming. When the volume average particle size of the foamable resin particles is greater than 0.50 mm, for the foamable resin particles formed by foaming, when the foamable particles are filled into the molding machine, the filling property of the narrow space will deteriorate. It should be noted that the narrow space in the molding machine corresponds to a thinner portion in the obtained foamed molded body. In this specification, the volume average particle size of the foamable resin particles refers to: using a particle size analyzer (such as an image processing method Millitrac JPA particle size analyzer), the particle size of the foamable resin particles is measured on a volume basis, and the result is expressed as a cumulative distribution, and the volume accumulation becomes 50% of the particle size.

[0053] The present expandable resin particles have excellent expandability. The expandability of the expandable resin particles is evaluated by the heating time of the expandable resin particles until the expandable resin particles become expandable particles of a specified expansion ratio. In the present specification, the expandability of the expandable resin particles is evaluated by the heating time obtained by sequentially carrying out the following (1) to (3): (1) Adding expandable methyl methacrylate resin particles to a 100°C cooker and heating the expandable methyl methacrylate resin particles; (2) Taking out the methyl methacrylate foamed particles obtained by foaming the expandable methyl methacrylate resin particles from the cooker at regular intervals and measuring the expansion ratio of the methyl methacrylate foamed particles; (3) Measuring the time from adding the expandable methyl methacrylate resin particles to the cooker until the expandable methyl methacrylate foamed particles with an expansion ratio of 45 times are obtained, that is, the heating time of the expandable methyl methacrylate resin particles. Here, the expansion ratio of the methyl methacrylate foamed particles is the value obtained by sequentially carrying out the following (1) to (3): (1) 10 g of methyl methacrylate foamed particles are weighed and added to 1000 cm 3 (2) according to the scale of the measuring cylinder, measure the volume of 10g of methyl methacrylate foamed particles; (3) using the following formula, calculate the expansion ratio of the methyl methacrylate foamed particles;

[0054] Foaming ratio (cm 3 / g) = volume of foamed particles (cm 3 ) / 10g.

[0055] In this specification, the expansion ratio of methyl methacrylate foamed particles is calculated by the above method, so it can also be called volume ratio. In addition, based on the above formula, the unit of the expansion ratio is actually cm 3 / g, but in this specification, the unit of the expansion ratio is expressed as "times" for convenience.

[0056] The shorter the heating time, the better the foamability of the foamable resin particles. The heating time measured as described above of the foamable resin particles is preferably less than 6 minutes, more preferably less than 5 minutes and 30 seconds, more preferably less than 5 minutes, further preferably less than 4 minutes and 30 seconds, and particularly preferably less than 4 minutes. Through this configuration, the foamable resin particles can provide a foaming molding with better surface quality.

[0057] [3. Method for producing expandable methyl methacrylate resin particles]

[0058] A method for producing expandable methyl methacrylate resin particles according to one embodiment of the present invention comprises: a copolymerization step of copolymerizing a monomer mixture containing methyl methacrylate monomers and acrylate monomers, and a blowing agent impregnation step of impregnating the obtained copolymer with a blowing agent. The copolymerization step further comprises: (a) a starting step of starting the copolymerization of the monomer mixture in the presence of 0.20 to 1.20 parts by weight of a first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture, and (b) after the starting step, at a time point when the polymerization conversion rate is 35% to 70%, an adding step of adding 0.08 to 0.50 parts by weight of a second sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture to the reaction mixture. In the copolymerization step, the amount of the methyl methacrylate monomer is 90.0 to 99.0 parts by weight, and the amount of the acrylate monomer is 1.0 to 10.0 parts by weight, based on 100 parts by weight of the total amount of the methyl methacrylate monomer and the acrylate monomer.

[0059] In the present specification, the term "poorly water-soluble inorganic salt" means an inorganic salt having a solubility in water at 25°C of 0.1 mg / ml or less.

[0060] Hereinafter, “the method for producing expandable methyl methacrylate resin particles according to one embodiment of the present invention” may also be referred to as “the present production method”.

[0061] The present manufacturing method has the aforementioned structure, and thus can provide a foamable methyl methacrylate resin particle, which can provide a foamed molded body with excellent surface quality and less residue during combustion. In addition, the present manufacturing method has the aforementioned structure, and thus has the advantage of being able to provide the present foamable resin particles recorded in item [2. Foamable methyl methacrylate resin particles]. That is, the present manufacturing method can be suitably used to manufacture the present foamable resin particles recorded in item [2. Foamable methyl methacrylate resin particles]. It should be noted that the "copolymer" in the present manufacturing method is equivalent to the "base resin" contained in the foamable resin particles recorded in item [2. Foamable methyl methacrylate resin particles].

[0062] Hereinafter, each step related to the present production method will be described. In addition to the matters described in detail below, the description of the item [2. Expandable methyl methacrylate resin particles] is also appropriately cited. In addition, the present expandable resin particles described in the item [2. Expandable methyl methacrylate resin particles] are preferably produced by the present production method, but can also be produced by a method other than the present production method. That is, the production method of the present expandable resin particles is not limited to the method of the present production method described below.

[0063] (3-1. Copolymerization step)

[0064] The copolymerization step in the present production method may be suspension polymerization in which a monomer mixture is polymerized in an aqueous suspension. Hereinafter, the copolymer (base resin) obtained by the copolymerization step may be simply referred to as "resin particles".

[0065] The "aqueous suspension" in the present invention refers to a liquid in which monomer droplets and / or resin particles are dispersed in water or an aqueous solution by stirring, etc. In the aqueous suspension, (a) a water-soluble surfactant and a monomer may be dissolved, and (b) a water-insoluble dispersant, a polymerization initiator, a chain transfer agent, a crosslinking agent, a bubble regulator, a flame retardant, a solvent, a plasticizer, etc. may be dispersed together with the monomer.

[0066] The weight ratio of the monomer and polymer (resin) to water or aqueous solution in the aqueous suspension is preferably 1.0 / 0.6 to 1.0 / 3.0, based on the ratio of the obtained methyl methacrylate resin to water or aqueous solution. It should be noted that the "aqueous solution" mentioned here means a solution formed by water and components other than the methyl methacrylate resin.

[0067] The copolymerization step includes a starting step of starting the copolymerization of the monomer mixture in the presence of 0.20 to 1.20 parts by weight of the first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture. The starting step is, for example, a step of starting the copolymerization of the monomer mixture using an aqueous suspension containing (a) water, (b) a monomer mixture containing a methyl methacrylate monomer and an acrylate monomer, (c) 0.20 to 1.20 parts by weight of the first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture, (d) a crosslinking agent, and optionally (e) a polymerization initiator, a surfactant, a dispersant other than the sparingly water-soluble inorganic salt, a chain transfer agent, a bubble regulator, a flame retardant, a solvent, and a plasticizer.

[0068] In this specification, “before the start of polymerization reaction” may be referred to as “initial polymerization.” The first sparingly water-soluble inorganic salt and the optionally added polymerization initiator mixed (added) into the aqueous suspension in the initial step may be regarded as substances (raw materials) used in the initial polymerization.

[0069] In the initial step, the first sparingly water-soluble inorganic salt can function as a dispersant. Examples of the first sparingly water-soluble inorganic salt used in the initial step, i.e., the initial polymerization step, include tricalcium phosphate, magnesium pyrophosphate, hydroxyapatite, kaolin, and the like.

[0070] In the initial step, (a) a water-soluble polymer such as polyvinyl alcohol, methylcellulose, polyacrylamide, polyvinyl pyrrolidone, and / or (b) an anionic surfactant such as sodium α-olefin sulfonate, sodium dodecylbenzene sulfonate, etc. may be used together with the first sparingly water-soluble inorganic salt.

[0071] As the first sparingly water-soluble inorganic salt used in the starting step, tricalcium phosphate is preferred from the viewpoint of the ability to protect the resin particles and / or the monomer droplets. From the viewpoint of the dispersion stability of the droplets, the starting step is preferably a step of starting the copolymerization of the monomer mixture in the presence of tricalcium phosphate as the sparingly water-soluble inorganic salt and sodium α-olefin sulfonate as the anionic surfactant.

[0072] The starting step is preferably the following step: in the presence of the first sparingly water-soluble inorganic salt, preferably 0.20 to 1.20 parts by weight, more preferably 0.20 to 1.10 parts by weight, and further preferably 0.40 to 1.10 parts by weight, relative to 100 parts by weight of the monomer mixture, the copolymerization of the monomer mixture is started. When the copolymerization of the monomer mixture is started in the presence of 0.20 parts by weight or more of the first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture, there is no concern that the volume average particle size of the obtained foamable resin particles becomes too large. When the copolymerization of the monomer mixture is started in the presence of 1.10 parts by weight or less of the first sparingly water-soluble inorganic salt relative to 100 parts by weight of the monomer mixture, there is no concern that a large amount of microparticles of the foamable resin particles are generated. That is, by starting the copolymerization of the monomer mixture in the presence of the first sparingly water-soluble inorganic salt in an amount within the above range, foamable resin particles having a desired volume average particle size can be obtained in good yield.

[0073] In the initial step, when a water-soluble polymer and / or anionic surfactant is used together with the first sparingly water-soluble inorganic salt, the concentration of the water-soluble polymer and / or anionic surfactant in the aqueous suspension is preferably 30 ppm to 100 ppm based on the concentration of the monomer mixture.

[0074] The copolymerization step includes the following adding step: after the starting step, when the polymerization conversion rate reaches 35% to 70%, 0.08 to 0.50 parts by weight of the second sparingly water-soluble inorganic salt is added to the reaction mixture based on 100 parts by weight of the monomer mixture.

[0075] In this specification, “after the start of the polymerization reaction” may be referred to as “during the polymerization.” The second sparingly water-soluble inorganic salt added to the reaction mixture in the adding step may also be referred to as a substance (raw material) used during the polymerization.

[0076] When the polymerization (copolymerization) of the monomer mixture in the copolymerization step is performed by suspension polymerization, the reaction mixture in the adding step can also be said to be an aqueous suspension.

[0077] In the addition process, the second sparingly water-soluble inorganic salt can function as a dispersant. As the second sparingly water-soluble inorganic salt used in the addition process, i.e., during the polymerization, the substances exemplified as the first sparingly water-soluble inorganic salt can be cited. As the second sparingly water-soluble inorganic salt, it is preferred to select one or more from the group consisting of tricalcium phosphate, hydroxyapatite and kaolin, and tricalcium phosphate is more preferred. This configuration has the advantage of preventing the aggregation of the resin particles after the addition (addition) of the dispersant, and obtaining resin particles of the target particle size.

[0078] The adding step is preferably a step in which, after the starting step, at a time point when the polymerization conversion rate is 35% to 70%, 0.08 to 0.50 parts by weight, more preferably 0.10 to 0.50 parts by weight, more preferably 0.10 to 0.40 parts by weight, further preferably 0.10 to 0.30 parts by weight, and particularly preferably 0.10 to 0.20 parts by weight of the second sparingly water-soluble inorganic salt is added to the reaction mixture relative to 100 parts by weight of the monomer mixture at a time point in which the polymerization conversion rate is 35% to 70%. In the adding step, when 0.08 parts by weight or more of the second sparingly water-soluble inorganic salt is added to the reaction mixture relative to 100 parts by weight of the monomer mixture, there is no concern that the volume average particle size of the obtained foamable resin particles becomes too large. In the adding step, when 0.50 parts by weight or less of the second sparingly water-soluble inorganic salt is added to the reaction mixture relative to 100 parts by weight of the monomer mixture, there is no increase in production cost due to excessive use of the sparingly water-soluble inorganic salt. That is, in the adding step, by adding the second sparingly water-soluble inorganic salt in an amount within the above range to the reaction mixture, expandable resin particles having a desired volume average particle size can be obtained at a low production cost.

[0079] The addition step is preferably: preferably, the second sparingly water-soluble inorganic salt is added to the reaction mixture at a time point when the polymerization conversion rate is 35% to 70%, more preferably at a time point when the polymerization conversion rate is 40% to 50%. With this configuration, expandable resin particles having a desired volume average particle size can be obtained. The method for measuring the polymerization conversion rate in this specification is described in detail in the following examples.

[0080] The copolymerization step preferably varies the polymerization temperature and is implemented in at least two stages. For convenience, the two polymerization steps with different polymerization temperatures are referred to as the first polymerization step and the second polymerization step below. The copolymerization step can also be said to preferably include the first polymerization step and the second polymerization step with different polymerization temperatures, which are continuous.

[0081] The copolymerization step preferably includes, for example: (a) a first polymerization step, which is carried out at a polymerization temperature of 70° C. to 90° C. and using a low-temperature decomposition type polymerization initiator; and (b) a second polymerization step, which is carried out continuously with the first polymerization step, at a polymerization temperature higher than that of the first polymerization step (e.g., 90° C. to 110° C.) and using a high-temperature decomposition type polymerization initiator. In the copolymerization step, it is preferred that the main polymerization reaction is carried out in the first polymerization step, and the residual monomer is reduced in the second polymerization step.

[0082] As the polymerization initiator, a free radical generation type polymerization initiator used in the manufacture of conventional thermoplastic polymers can be used. Representative free radical generation type polymerization initiators include, for example, (a) organic peroxides such as benzoyl peroxide, lauroyl peroxide, tert-butyl peroxybenzoate, isopropyl-tert-butyl peroxycarbonate, butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyisopropyl carbonate, di-tert-butyl peroxyhexahydroterephthalate, 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and tert-butylperoxy-2-ethylhexyl monocarbonate, and (b) azo compounds such as azobisisobutyronitrile and azobis(dimethylvaleronitrile). These polymerization initiators may be used alone or in combination of two or more.

[0083] Among the above-mentioned free radical generating polymerization initiators, (a) benzoyl peroxide, lauroyl peroxide, tert-butyl peroxypivalate, di-tert-butyl perhexahydroterephthalate, azobisisobutyronitrile and azobis(dimethylvaleronitrile) are low temperature decomposition type polymerization initiators, and (b) tert-butyl peroxybenzoate, isopropyl-tert-butyl peroxycarbonate, butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxyisopropyl carbonate, 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane and tert-butylperoxy-2-ethylhexyl monocarbonate are high temperature decomposition type polymerization initiators.

[0084] The amount of the polymerization initiator used is preferably 0.1 to 0.5 parts by weight based on 100 parts by weight of the monomer mixture, which is the sum of the amounts used in the first polymerization step and the second polymerization step. With this configuration, expandable resin particles having excellent expandability can be obtained.

[0085] The starting step (a) may be a step of starting copolymerization of the monomer mixture in the presence of the first sparingly water-soluble inorganic salt, a low-temperature decomposition type polymerization initiator, and a high-temperature decomposition type polymerization initiator, and (b) may be a step of starting copolymerization of the monomer mixture in the presence of the first sparingly water-soluble inorganic salt and a low-temperature decomposition type polymerization initiator. When the starting step is a step of starting copolymerization of the monomer mixture in the presence of the first sparingly water-soluble inorganic salt and a low-temperature decomposition type polymerization initiator, the high-temperature decomposition type polymerization initiator may be added to the reaction mixture (aqueous suspension) after the starting step, i.e., during the polymerization.

[0086] In the copolymerization process, a chain transfer agent is preferably used. As a chain transfer agent, there is no particular limitation, and the known substances used in the polymerization of methyl methacrylate resins can be used. As a chain transfer agent, monofunctional chain transfer agents such as (a) alkyl mercaptans and thioglycolates and (b) polyfunctional chain transfer agents formed by esterifying polyol hydroxyls such as ethylene glycol, neopentyl glycol, trimethylolpropane, sorbitol using thioglycolic acid or 3-mercaptopropionic acid. As alkyl mercaptans, n-octyl mercaptan, n-dodecyl mercaptan and tert-dodecyl mercaptan can be mentioned. The amount of the chain transfer agent is preferably 0.1 parts by weight or more and less than 0.5 parts by weight relative to 100 parts by weight of the substrate resin.

[0087] (3-2. Foaming agent impregnation step)

[0088] In the blowing agent impregnation step, the methyl methacrylate resin particles, which are the copolymer obtained in the copolymerization step, are impregnated with the blowing agent, thereby obtaining expandable methyl methacrylate resin particles.

[0089] The blowing agent impregnation step may be performed at any time, and may be performed, for example, together with the second polymerization step or after the second polymerization step.

[0090] The foaming agent impregnation process preferably causes the foaming agent to be impregnated into the obtained copolymer at a time point when the polymerization conversion rate from the monomer to the copolymer is 80% to 95%. When the foaming agent is impregnated into the copolymer at a time point when the polymerization conversion rate is 80% or more, the foaming agent moderately impregnates into the interior of the copolymer, so there is no concern about the occurrence of aggregation between the copolymers caused by the softening of the copolymer, and the manufacturing yield is good. When the foaming agent is impregnated into the copolymer at a time point when the polymerization conversion rate is less than 95%, the foaming agent fully infiltrates into the interior of the copolymer, so there is no concern about the formation of a double bubble structure (hard core) in the foamed particles formed by foaming the obtained foamable resin particles. As a result, by in-mold molding of the foamed particles, a foamed molded body with excellent surface quality can be obtained.

[0091] In the step of impregnating the methyl methacrylate resin particles as the copolymer, the amount of the foaming agent impregnated therein is the same as the content of the foaming agent in the foamable resin particles described in the section (foaming agent) of [2. Foamable methyl methacrylate resin particles], including a preferred embodiment. With this configuration, foamable resin particles having sufficient foamability can be obtained, and the copolymer does not aggregate in the step of impregnating the foaming agent, so that the foamable resin particles can be safely produced.

[0092] In the blowing agent impregnation step, the treatment temperature (also referred to as impregnation temperature) and the treatment time (also referred to as impregnation time) when impregnating the copolymer with the blowing agent are not particularly limited.

[0093] In the foaming agent impregnation process, the impregnation temperature when the foaming agent is impregnated into the copolymer is preferably below 95°C to 120°C, and more preferably below 100°C to 117°C. When the impregnation temperature is above 95°C, the foaming agent fully penetrates into the interior of the copolymer, so there is no concern about the formation of a double bubble structure (hard core) in the foamed particles obtained by foaming the foamable resin particles. As a result, by in-mold molding of the foamed particles, a foamed molded body with excellent surface quality can be obtained. When the impregnation temperature is below 120°C, the pressure in the polymerization machine will not become too high, so there is no need to use heavy impregnation equipment that can withstand huge pressures to obtain foamable resin particles that can provide foamed particles with a uniform bubble structure.

[0094] In the present production method, when a solvent (for example, a solvent having a boiling point of 50° C. or higher) is used, the solvent is preferably added to the reaction mixture (aqueous suspension) immediately before or simultaneously with the blowing agent impregnation step.

[0095] [4. Methyl methacrylate foam particles]

[0096] The methyl methacrylate foamed particles according to one embodiment of the present invention are foamed particles obtained by foaming the foamable methyl methacrylate resin particles described in [2. Foamable methyl methacrylate resin particles] or the foamable methyl methacrylate resin particles produced by the production method described in [3. Production method of foamable methyl methacrylate resin particles].

[0097] Hereinafter, “methyl methacrylate-based expanded beads according to one embodiment of the present invention” may also be referred to as “present expanded beads”.

[0098] The present expandable resin particles can be made into expandable particles by a common expansion method. Specifically, for example, by sequentially performing the following operations (1) to (3), methyl methacrylate expandable particles can be obtained: (1) adding expandable methyl methacrylate resin particles into a container equipped with a stirrer; (2) heating the expandable methyl methacrylate resin particles using a heat source such as steam; (3) expanding the expandable methyl methacrylate resin particles to a desired expansion ratio by the above-mentioned (2) to obtain methyl methacrylate expandable particles.

[0099] The foaming of the expandable methyl methacrylate resin particles can also be said to be preparatory foaming for obtaining the methyl methacrylate foamed molded article described later from the expandable methyl methacrylate resin particles. Therefore, the foaming of the expandable methyl methacrylate resin particles is sometimes referred to as "pre-foaming", and the methyl methacrylate foamed particles are sometimes referred to as "methyl methacrylate pre-foamed particles".

[0100] The filling property of the foamed particles is excellent. The filling property of the foamed particles is evaluated by the volume of the foamed particles that actually enter the container when the foamed particles are added to a container of a specified shape and size. In this specification, the filling property of the foamed particles is evaluated by the volume obtained by sequentially implementing the following (1) to (3): (1) adding methyl methacrylate foamed particles with a foaming ratio of 45 times to a container with a length of 120 mm, a width of 80 mm and a thickness of 6 mm; (2) adding (transferring) the methyl methacrylate foamed particles in the container to a measuring cylinder; (3) measuring the volume of the methyl methacrylate foamed particles according to the scale lines on the measuring cylinder.

[0101] The larger the volume is, the better the filling property of the foamed beads is. The volume of the foamed beads measured as described above is preferably 50 cm 3 More than 51 cm 3 Above, particularly preferably 52cm 3 With this configuration, the foamed beads can provide a foamed molded body having a more excellent surface quality.

[0102] [5. Methyl methacrylate foamed products]

[0103] The methyl methacrylate foamed molded article according to one embodiment of the present invention is a foamed molded article obtained by in-mold molding the methyl methacrylate foamed particles described in [4. Methyl methacrylate foamed particles].

[0104] Hereinafter, the "methyl methacrylate-based foamed molded article according to one embodiment of the present invention" may also be referred to as the "present foamed molded article".

[0105] The foamed particles are formed by a common in-mold forming method to form a foamed molded article. Specifically, for example, the methyl methacrylate foamed molded article can be obtained by sequentially performing the following operations (1) to (3): (1) filling a closable but not airtight mold with methyl methacrylate foamed particles; (2) heating the methyl methacrylate foamed particles with water vapor; (3) fusing the methyl methacrylate foamed particles to each other by the above-mentioned (2), thereby obtaining a methyl methacrylate foamed molded article.

[0106] The surface quality of the methyl methacrylate foaming molding of one embodiment of the present invention is excellent. In addition, the methyl methacrylate foaming molding of one embodiment of the present invention has the advantage of few residues when the foaming molding is buried in the foundry sand and the molten metal is flowed into the foaming molding, thereby the foaming molding and the metal are replaced. Based on these reasons, the methyl methacrylate foaming molding of one embodiment of the present invention can be suitably used as lost foam.

[0107] 〔6. Lost foam〕

[0108] The lost foam according to one embodiment of the present invention includes the methyl methacrylate-based foamed molded article described in [5. Methyl methacrylate-based foamed molded article].

[0109] The lost foam according to one embodiment of the present invention has excellent surface quality and produces little residue during combustion, and therefore can be suitably used in various metal castings.

[0110] One embodiment of the present invention may have the following configuration.

[0111] (1) Expandable methyl methacrylate resin particles comprising a base resin and a foaming agent, wherein the base resin comprises a methyl methacrylate unit, an acrylate unit, and a crosslinking agent-derived structural unit as structural units, the expandable methyl methacrylate resin particles having a volume average particle size of 0.30 mm to 0.50 mm, and wherein the base resin (a) contains 90.0 to 99.0 parts by weight and 1.0 to 10.0 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, and (b) contains 0.05 to 0.20 parts by weight of the crosslinking agent-derived structural unit, relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, and (c) contains 2.5 parts by weight or less of the structural unit derived from an aromatic vinyl compound, relative to 100 parts by weight of the base resin.

[0112] (2) The expandable methyl methacrylate resin particles according to (1), wherein the acrylic acid ester is butyl acrylate.

[0113] (3) Methyl methacrylate foamed particles obtained by foaming the foamable methyl methacrylate resin particles described in (1) or (2).

[0114] (4) A methyl methacrylate foamed molded article obtained by in-mold molding the methyl methacrylate foamed particles described in (3).

[0115] (5) A lost foam comprising the methyl methacrylate-based foamed molded article described in (4).

[0116] Example

[0117] Examples and comparative examples are given below, but the present invention is not limited thereto.

[0118] (Polymerization Conversion Rate of Expandable Methyl Methacrylate Resin Particles)

[0119] During the polymerization, the aqueous suspension was sampled and filtered. The weight of the resin component remaining on the filter paper was measured, and the obtained weight was taken as the weight before heating. Then, after adding a polymerization inhibitor to the resin component, the resin component was heated at 150°C for 30 minutes to remove the volatile components. After that, the weight of the obtained resin component was measured, and the obtained weight was taken as the weight after heating. The polymerization conversion rate was calculated using the following formula.

[0120] Polymerization conversion rate (%) = weight after heating / weight before heating×100.

[0121] (Volume Average Particle Diameter of Expandable Methyl Methacrylate Resin Particles)

[0122] The particle size of the expandable methyl methacrylate resin particles was measured on a volume basis using a Millitrac JPA particle size analyzer with an image processing system. The obtained results were expressed as cumulative distribution, and the particle size at which the volume accumulation was 50% was defined as the volume average particle size.

[0123] (Foamability of Foamable Methyl Methacrylate Resin Particles)

[0124] The following (1) to (3) are performed in sequence: (1) the expandable methyl methacrylate resin particles are placed in a 100° C. steam cooker to heat the expandable methyl methacrylate resin particles; (2) the expandable methyl methacrylate resin particles are taken out of the steam cooker at regular intervals to obtain expandable methyl methacrylate particles having an expansion ratio of 45 times; (3) the time from the time the expandable methyl methacrylate resin particles are placed in the steam cooker to the time when expandable methyl methacrylate particles having an expansion ratio of 45 times are obtained, i.e., the heating time of the expandable methyl methacrylate resin particles is measured. The expandability of the expandable methyl methacrylate resin particles is evaluated based on the following criteria according to the obtained heating time.

[0125] ◎(Excellent): Heating time is less than 4 minutes

[0126] ○ (good): Heating time is 4 minutes or more and less than 6 minutes

[0127] × (bad): The heating time is 6 minutes or more.

[0128] Here, the following (1) to (3) are carried out in sequence to obtain the expansion ratio of the methyl methacrylate foamed particles: (1) 10 g of methyl methacrylate foamed particles are weighed and placed in a 1000 cm 3(2) according to the scale of the measuring cylinder, measure the volume of 10g of methyl methacrylate foamed particles; (3) using the following formula, calculate the expansion ratio of the methyl methacrylate foamed particles;

[0129] Foaming ratio (cm 3 / g) = volume of foamed particles (cm 3 ) / 10g.

[0130] (Filling properties of methyl methacrylate foamed particles)

[0131] The following (1) to (3) were performed in sequence: (1) methyl methacrylate foamed particles with a foaming ratio of 45 times were placed in a container with a length of 120 mm, a width of 80 mm, and a thickness of 6 mm; (2) the methyl methacrylate foamed particles in the container were placed in (transferred to) a measuring cylinder; (3) the volume of the methyl methacrylate foamed particles was measured according to the scale lines of the measuring cylinder. The filling property of the methyl methacrylate foamed particles was evaluated based on the obtained volume according to the following criteria.

[0132] ◎(Excellent): Volume is 52cm 3 above

[0133] ○ (good): Volume is 50cm 3 Over and under 52cm 3

[0134] ×(Defective): Volume less than 50cm 3 .

[0135] (Shrinkage of Methyl Methacrylate Foamed Particles)

[0136] Using a pressurized pre-foaming machine "BHP manufactured by Daikai Industry Co., Ltd.", the expandable methyl methacrylate resin particles were foamed under a blowing steam pressure of 0.12 to 0.16 MPa to obtain methyl methacrylate foamed particles with a foaming ratio of 45 times. Through this operation, methyl methacrylate foamed particles with a foaming ratio of 45 times were obtained. After the obtained methyl methacrylate foamed particles were placed at room temperature (about 23°C) for 1 day, the degree of shrinkage of the surface of the methyl methacrylate foamed particles was observed. Based on the following criteria, the shrinkage of the methyl methacrylate foamed particles was evaluated according to the observation results of the surface of the methyl methacrylate foamed particles.

[0137] ⊚ (Excellent): No wrinkles were observed on the surface of the methyl methacrylate foamed particles by visual observation, and the surface was glossy.

[0138] ○ (good): No wrinkles were observed on the surface of the methyl methacrylate foamed particles by visual observation, and no gloss was observed on the surface.

[0139] × (bad): Wrinkles were observed visually on the surface of the methyl methacrylate foamed particles.

[0140] (Surface quality of methyl methacrylate foamed product)

[0141] The surface state of the methyl methacrylate-based foamed molded article was visually observed. The surface quality of the methyl methacrylate-based foamed molded article was evaluated based on the following criteria based on the observation results.

[0142] ◎ (Excellent): There is almost no gap between particles on the surface, that is, the surface is very beautiful

[0143] ○ (good): There are few gaps between particles on the surface, that is, the surface is beautiful

[0144] × (poor): There are many gaps between particles on the surface, that is, the surface appearance is poor.

[0145] (Evaluation of Residues during Combustion of Methyl Methacrylate Foamed Molded Article)

[0146] Use a gas burner to ignite about 7g (about 300cm 3 ) is a methyl methacrylate based foaming molding, the methyl methacrylate based foaming molding is burned, and the ash generation situation during the combustion is observed by visual observation. Based on the following benchmark, the residue during the combustion of the methyl methacrylate based foaming molding is evaluated according to the observation result of the ash.

[0147] ◎ (Excellent): Almost no dust is generated

[0148] ○ (good): produces a small amount of ash

[0149] × (bad): A large amount of dust was generated.

[0150] (Example 1)

[0151] In a 6L autoclave equipped with a stirrer, 150 parts by weight of water, 0.53 parts by weight of tricalcium phosphate as the first sparingly water-soluble inorganic salt, 0.0075 parts by weight of sodium α-olefin sulfonate, 0.08 parts by weight of lauroyl peroxide, 0.1 parts by weight of 1,1-di(tert-butylperoxy)cyclohexane, 0.1 parts by weight of 1,6-hexanediol diacrylate as a crosslinking agent, and 0.24 parts by weight of n-dodecyl mercaptan were added to prepare a mixed solution containing the first sparingly water-soluble inorganic salt. Subsequently, (a) 95 parts by weight of methyl methacrylate and 5 parts by weight of butyl acrylate as a monomer mixture, and (b) 1 part by weight of toluene were added to the mixed solution to prepare an aqueous suspension. Then, the temperature of the aqueous suspension was raised to 80°C to start polymerization, i.e., the start step was implemented. After 1 hour and 45 minutes after the start of polymerization (after the start step), the polymerization conversion rate was measured and the result was 43%. After 1 hour and 45 minutes had passed from the start of the polymerization (after the start step), 0.12 parts by weight of tricalcium phosphate as the second poorly water-soluble inorganic salt was added to the reaction mixture (aqueous suspension) to perform an adding step.

[0152] After a further 2 hours and 35 minutes, 1.5 parts by weight of cyclohexane and 9 parts by weight of n-butane-rich (the weight ratio of n-butane to isobutane in the n-butane-rich (n-butane / isobutane) is 70 / 30) as a foaming agent are added to the aqueous suspension. Thereafter, the temperature of the aqueous suspension is raised to 101°C. Then, the temperature of the aqueous suspension is maintained at 101°C for 10 hours, thereby performing polymerization and impregnation of the copolymer with the foaming agent (copolymerization step and foaming agent impregnation step). Thereafter, the aqueous suspension is cooled. After the aqueous suspension is cooled, the obtained product is washed, dehydrated and dried, thereby obtaining foamable methyl methacrylate resin particles.

[0153] The obtained expandable methyl methacrylate resin particles were sieved with sieves having mesh sizes of 0.355 mm and 0.600 mm. By this operation, expandable methyl methacrylate resin particles having a particle size of 0.355 mm to 0.600 mm were collected.

[0154] The obtained expandable methyl methacrylate resin particles were expanded using a pressurized pre-expanding machine "BHP, manufactured by Daikai Industry Co., Ltd." to obtain methyl methacrylate expanded particles having an expansion ratio of 45 times.

[0155] Then, the obtained methyl methacrylate foamed particles were molded in-mold using a KR-57 molding machine and a mold having a length of 450, a width of 300, and a thickness of 10 mm to obtain a methyl methacrylate foamed molded article.

[0156] The volume average particle size and foamability of the expandable methyl methacrylate resin particles, the filling property and shrinkage property of the methyl methacrylate foamed particles, and the surface quality and combustion residue of the methyl methacrylate foamed molded article were evaluated by the above-mentioned method. The evaluation results are shown in Table 1.

[0157] (Example 2)

[0158] The same operation as in Example 1 was carried out except that the monomer mixture used was changed to 97 parts by weight of methyl methacrylate and 3 parts by weight of butyl acrylate to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0159] (Example 3)

[0160] The same operation as in Example 1 was carried out except that the monomer mixture used was changed to 93 parts by weight of methyl methacrylate and 7 parts by weight of butyl acrylate to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0161] (Example 4)

[0162] The same operation as in Example 1 was carried out except that the monomer mixture used was changed to 94.5 parts by weight of methyl methacrylate and 5.5 parts by weight of methyl acrylate to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0163] (Example 5)

[0164] The same operation as in Example 1 was carried out except that the amount of 1,6-hexanediol diacrylate used as a crosslinking agent was changed to 0.06 parts by weight to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0165] (Example 6)

[0166] The same operation as in Example 1 was carried out except that the amount of 1,6-hexanediol diacrylate used as a crosslinking agent was changed to 0.18 parts by weight to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0167] (Example 7)

[0168] In the initial step, the amount of tricalcium phosphate as the first sparingly water-soluble inorganic salt was changed to 1.05 parts by weight. The same operation as in Example 1 was performed to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0169] (Example 8)

[0170] In the initial step, the amount of tricalcium phosphate as the first sparingly water-soluble inorganic salt was changed to 0.41 parts by weight. The same operation as in Example 1 was performed to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0171] (Example 9)

[0172] The same operation as in Example 1 was carried out except that 1.0 part by weight of styrene was used as an aromatic vinyl compound to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0173] (Comparative Example 1)

[0174] The same operation as in Example 1 was carried out except that the monomer mixture used was changed to 100 parts by weight of methyl methacrylate and 0 parts by weight of butyl acrylate to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0175] (Comparative Example 2)

[0176] The same operation as in Example 1 was carried out except that the monomer mixture used was changed to 88 parts by weight of methyl methacrylate and 12 parts by weight of butyl acrylate to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0177] (Comparative Example 3)

[0178] The same operation as in Example 1 was carried out except that the amount of 1,6-hexanediol diacrylate used as a crosslinking agent was changed to 0 parts by weight to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0179] (Comparative Example 4)

[0180] The same operation as in Example 1 was carried out except that the amount of 1,6-hexanediol diacrylate used as a crosslinking agent was changed to 0.22 parts by weight to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0181] (Comparative Example 5)

[0182] In the initial step, the amount of tricalcium phosphate as the first sparingly water-soluble inorganic salt was changed to 0.17 parts by weight. The same operation as in Example 1 was performed to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0183] (Comparative Example 6)

[0184] The same operation as in Example 1 was carried out except that 3.0 parts by weight of styrene was used as an aromatic vinyl compound to obtain expandable resin particles, expandable particles, and an expandable molded article. Each evaluation item was evaluated in the same manner as in Example 1. The evaluation results are shown in Table 2.

[0185] [Table 1]

[0186]

[0187] [Table 2]

[0188]

[0189] Industrial Applicability

[0190] According to one embodiment of the present invention, a foamable methyl methacrylate resin particle can be provided, which can provide a foamed molded body with excellent surface quality and little residue when burned. Therefore, one embodiment of the present invention can be suitably used as a lost foam when metal casting is performed by a solid mold casting method.

Claims

1. A foamable methyl methacrylate resin particle comprising a base resin and a foaming agent, The base resin comprises a methyl methacrylate unit, an acrylate unit and a structural unit derived from a crosslinking agent as structural units, The expandable methyl methacrylate resin particles have a volume average particle size of 0.30 mm to 0.45 mm, and when expanded at 100° C., the time until the expansion ratio reaches 45 times is less than 6 minutes. In the base resin, (a) relative to 100 parts by weight of the total amount of the methyl methacrylate units and the acrylate units, the content of the methyl methacrylate units is 90.0 parts by weight to 99.0 parts by weight, and the content of the acrylate units is 1.0 parts by weight to 10.0 parts by weight, (b) the content of the structural unit derived from the crosslinking agent is 0.05 parts by weight or more and less than 0.20 parts by weight relative to 100 parts by weight of the total amount of the methyl methacrylate unit and the acrylate unit, and (c) the content of the structural unit derived from the aromatic vinyl compound is 2.5 parts by weight or less relative to 100 parts by weight of the base resin, The acrylate unit is a butyl acrylate unit. 2 . Methyl methacrylate foamed particles obtained by foaming the foamable methyl methacrylate resin particles according to claim 1 .

3. A methyl methacrylate foamed molded article, which is obtained by in-mold molding of the methyl methacrylate foamed particles according to claim 2.

4. A lost foam comprising the methyl methacrylate-based foamed molded article according to claim 3.